2008
DOI: 10.1016/j.physa.2007.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and uncertainty in multislit matter wave diffraction

Abstract: We show that single and multi-slit experiments involving matter waves may be constructed to assess correlations between the position and momentum of a single free particle. These correlations give rise to position dependent phases which develop dynamically and may play an important role in the interference patterns. For large enough transverse coherence length such interference patterns are noticeably different from those of a classical dispersion free wave.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In Ref. [14] the authors explore the effect of the position-momentum correlations on the interference pattern but they do not take into account the influence of the propagation time from the double-slit to the screen. They also do not discuss the behavior of the correlations as a function of the propagation time from the source to the double-slit (or equivalently, the behavior of the correlations as a function of the parameter σ 0 ).…”
Section: Intensity Visibility and Predictabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [14] the authors explore the effect of the position-momentum correlations on the interference pattern but they do not take into account the influence of the propagation time from the double-slit to the screen. They also do not discuss the behavior of the correlations as a function of the propagation time from the source to the double-slit (or equivalently, the behavior of the correlations as a function of the parameter σ 0 ).…”
Section: Intensity Visibility and Predictabilitymentioning
confidence: 99%
“…The qualitative changes in the interference pattern as a function of the increasing in the position-momentum correlations was studied in [15]. In addition, other studies have shown that the Gouy phase of matter waves is directly related to the position-momentum correlations, as studied for the first time in [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In this section we discuss double-slit interference of matter waves, for instance neutrons or fullerene molecules [35], to illustrate the ideas that we discussed so far. Consider the experimental set up illustrated in the Fig.…”
Section: Double Slit Interference: Complementarity Principle and The mentioning
confidence: 99%
“…An analytical expression for P B and P C can in principle be derived in terms of the parameters as illustrated in Fig. 3 as performed in [35] but it is not essential to the purposes of our discussion.…”
Section: I(y Tmentioning
confidence: 99%
“…The reader is referred to Refs. [11][12][13][14] for details and implementation examples of the truncation approximation.…”
Section: Introductionmentioning
confidence: 99%